KADAR HARA DALAM JARINGAN TANAMAN SEBAGAI RESPON BUDIDAYA MONOKULTUR DAN HUBUNGANNYA DENGAN HASIL PADA TANAMAN TEBU - Anna Kusumawati; Eko Hanudin; Benito Heru Purwanto; Makruf Nurudin (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[RESPONSE OF THE NUTRITION LEVELS OF SUGARCANE IN THREE ORDERS OF SOIL DUE TO SUGARCANE MONOCULTURE CULTIVATION]. Monoculture cultivation will have an influence not only on soil conditions but also on plant growth, nutrient levels in plant tissues, and yields. The purpose of this study was (1)  to determine the effect of monoculture sugarcane cultivation on nutrient levels of the roots, stalks, and leaves of sugarcane plants, (2) to determine the relationship between nutrient levels in sugarcane tissue and sugarcane productivity, and yield in three different soil orders. This research had two factors, namely soil order (Entisol, Inceptisol, and Vertisol) and sugarcane monoculture period (1–10, 11–20, and 21–30 years). The sugar cane used was the ratoon of two sugarcane. Parameters observed included nutrient levels of N, P, K, B, and Zn in roots, stalks, and leaves of sugarcane, and productivity of plants. Data analysis was performed with ANOVA at 5% level and regression correlation analysis. The results showed that the levels of N (leaves, stalks, and roots), levels of P (leaves, stalks, and roots), levels of leaf K, levels of B (leaves and roots), and level of Zn of sugarcane roots were influenced by the interaction between soil order and sugarcane monoculture period. Zn and K levels in sugarcane leaves had a strong and significant correlation with sugarcane productivity (r=0.778* and r=0.699*), while sugarcane yields had a strong and significant correlation with N content of root (r=0.752*). This result indicates that the soil order and the mass of sugarcane monoculture have an effect on the nutrient content in the plant and this nutrient content affects the productivity and yield. The availability of macro and micronutrients needs to be considered in monoculture sugarcane planting techniques to obtain optimal and sustainable sugarcane yields.